Analisis Komunikasi Organisasi Antar Budaya Dalam AIESEC: Perspektif Teori Dan Praktik Berdasarkan Teori Komunikasi Organisasi Aliran Klasik Dan Human Behavior - Sabila Putri Sutrijadi; Rizang Conery; Nabihan Cahyadi Winafsi; Raka Prakasa (Kampus Akademik Publiser, 2024)
Organizational communication is an important aspect in the functioning of an organization, providing an understanding of the internal and external dynamics that affect its performance. AIESEC, a global organization that focuses on leadership development and cultural exchange among university students, presents an interesting case study. With a presence in 127 countries, including Indonesia, AIESEC shapes future leaders and contributes to national development through programs in line with the Sustainable Development Goals (SDGs). This research aims to analyze the structure of formal communication, the role of informal communication, and the psychological and social factors that influence communication within AIESEC. Qualitative methods were used with in-depth interviews, participatory observation, and document analysis to gain a holistic understanding. The results show that AIESEC combines classical communication principles with a human behavior approach, using organized formal structures and informal communication that supports collaboration. Communication technology also plays an important role in supporting organizational effectiveness. This study provides insights into the relationship between organizational communication theory and practice in AIESEC as well as recommendations for the improvement of communication strategies.